THE CHOICE OF INSTALLATION LOCATIONS OF THE DEVICES AND THE NUMBER OF ARRIVALS DURING THE TESTS, THE IMPACT ON THE PATH - Tikhov, M. S.; Romen, Yu. S.; Belousov, A. V. (Science and Transport Progress, 2007)
An analysis of existing approaches to defining the sites of installation of measuring devices and the number of runs for getting reliable information in rolling stock track impact tests has been performed. A method of correction of the number of runs and selection of the sites for installation of measuring devices on the tested track section has been offered.